The Use of Mantra Language in Traditional Healing Rituals of the Javanese Belumai II Community, Rejang Lebong Regency, Bengkulu Province - Endang Sariani; Randi Randi (JPI: Jurnal Pustaka Indonesia, 2023)
This study explores the linguistic forms, symbolic meanings, and cultural functions of healing mantras among the Javanese Belumai II community in Padang Ulak Tanding, Rejang Lebong Regency, Bengkulu Province, Indonesia. Using a qualitative descriptive design, data were collected through observation of rituals, interviews with three practitioners, and documentation of recited mantras, followed by hermeneutic analysis. The results identify seven mantras employed for healing, including those addressing spirit disturbances, child protection, eye disease, toothache, abscess, headache, and sorcery-related illness. Structurally, the mantras appear in two forms: poetic free-verse and pantun with ABAB rhyme schemes, both framed by Islamic invocations such as Bismillahirrahmanirrahim and Lailahaillallah. Symbolically, they embody prayers for divine intervention, protective commands, metaphoric persuasion, and performative declarations that reinforce cultural belief in healing. These findings demonstrate that mantras function as both therapeutic expressions and cultural acts, sustaining intangible heritage and communal identity. Compared with earlier studies that focused mainly on ritual or symbolism, this research offers novelty by systematically integrating form and meaning in one community context. The study implies the importance of safeguarding oral traditions, supporting culturally sensitive health policies, and enriching educational curricula, while acknowledging limitations in scope and suggesting broader, interdisciplinary research.